Interrelationships Between Quality of Work Life Dimensions: An Internal Consistency Analysis among Foundry Employees in Kolhapur - M. Patil, Swati; U. Tilave, Madhav; D. Kundale, Avadhut; D. Desai, Akshaykumar; S. Tribhuvan, Rachana (Journal of Neonatal Surgery, 2025)
A nation's prosperity hinges on the quality of its human capital. In the 21st century, businesses recognize that their competitive edge lies not solely in products or technology, but in the unique expertise, skills, and knowledge of their workforce. As economist Arthur Lewis poignantly noted, "there are great differences in development between countries which seem to have roughly equal resources." This underscores the crucial role employee well-being plays in national success. When individuals face challenges at work or home, their psychological well-being can suffer, impacting both their professional and personal lives. Work-life balance issues, for instance, can directly affect the quality of output in industries like foundry work. Recognizing this, the concept of Quality of Work Life (QWL) emphasizes tailoring work environments to meet employee needs, ultimately fostering both happiness and productivity.